PENGARUH KOMPETENSI, KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR FIANKA REZALINA FATMA PEKANBARU - Syaher Imanina Ilmi Siti; Marnis Marnis; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aimed to examine the effect of Competence, Compensation and JobSatisfaction on Employee Performance. This research was conducted at PT BPRFianka Rezalina Fatma Pekanbaru as the object of research. This study uses aquantitative and qualitative approach. The population of this study were allemployees of PT BPR Fianka Rezalina Fatma Pekanbaru so that from thepopulation a sample of 55 employees was obtained using the saturated samplemethod. The data analysis technique used in this research is multiple linearregression test. This research instrument used a questionnaire and analyzed usingSPSS. The results of the study show that employee competence, compensation andjob satisfaction have a positive and significant effect on employee performance. Keyword : Competence, Compensation, Job Satisfaction, Employee Performance